Preoperative and Intraoperative Factors as Predictors for Urological Injuries in Patients with Placenta Accreta Spectrum - Djusad, Suskhan; Dilmy, Mohammad Adya Firmansha; Pratama, Rendy Adhitya; Purwosunu, Yuditiya; Saroyo, Yudianto Budi; Fadhly, Raden Muhammad Ali (Current Women's Health Reviews, 2025)
Introduction/Background Placenta accreta is an abnormal total or partial invasion of the trophoblast to the myometrium of the uterus, with a prevalence of 1 in 1000 births globally in 2018. Surgical treatment of PAS is known to have a high risk of urological injury. No study reports preoperative and intraoperative factors related to urological injury, especially in Indonesia. Methods A case-control study was conducted at Cipto Mangunkusumo General Hospital, Indonesia. Data were obtained through medical records dated from January 2012 to December 2020. Pregnant women with PAS treated with surgical management were recruited. The selection of the case group consists of participants with urological injuries, while the control group involves participants with no urological injuries. The case and control groups were matched according to the general characteristics with a ratio of 1:1. Results Significant differences between groups were found in preoperative factors (history of urological symptoms, USG examination) and intraoperative factors (blood loss, multidisciplinary team, percreta placental invasion). Multivariate analysis showed an association between the history of urological symptoms and intraoperative bleeding to urological injury. Conclusion Preoperative factors such as ultrasonography examination and history of urological symptoms, along with intraoperative factors such as blood loss, multidisciplinary team, and degree of the placental invasion, were associated with urological injury in surgically treated PAS.
Keywords: hematuria